STEAM activities in 30 minutes for elementary learners - Rinio, Deborah (AASL standards-based learning., 2020)
"Using STEAM activities, this book places school librarians at the intersection with inquiry in an elementary school. Learners will think like a scientist and design like an engineer using an iterative process to make authentic learning connections and develop a growth mindset. Designed to be completed in 30-minute class periods, 14 scaffolded STEAM activities allow school librarians to easily shift the same lesson between classes and grade levels"--